Recent advancements in understanding fin regeneration in zebrafish. (14th November 2019) - Sehring, Ivonne M.; Weidinger, Gilbert
Abstract: Zebrafish have the remarkable ability to fully regenerate a lost appendage, faithfully restoring its size, shape and tissue patterning. Studies over the past decades have identified mechanisms underlying the formation, spatial organization, and regenerative growth of the blastema, a pool of proliferative progenitor cells. The patterning of newly forming tissue is tightly regulated to ensure proper rebuilding of anatomy. Precise niche regulation of retinoic acid and sonic hedgehog signaling ensures adherence to ray—interray boundaries. The molecular underpinnings of systems underlying re‐establishment of pre‐amputation size and shape (positional information) are also slowly starting to emerge. Osteoblasts play an important role as a cellular source of regenerating skeletal elements, and in zebrafish both osteoblast dedifferentiation as well as de novo osteoblast formation occurs. Both dedifferentiation and proliferation are tightly controlled, which makes it interesting to compare it to tumorigenesis, and to identify potential players involved in these processes. This article is categorized under: Adult Stem Cells, Tissue Renewal, and Regeneration > Regeneration Abstract : Zebrafish fins provide an excellent model to study cellular and molecular mechanisms of regeneration.